Lysine demethylase LSD1 is associated with stemness in EBV-positive B cell lymphoma - Joo Hyun Kim; Chaehwa Park; Won Seog Kim (Scientific Reports, 2024)
Abstract EBV-infected lymphoma has a poor prognosis and various treatment strategies are being explored. Reports suggesting that B cell lymphoma can be induced by epigenetic regulation have piqued interest in studying mechanisms targeting epigenetic regulation. Here, we set out to identify an epigenetic regulator drug that acts synergistically with doxorubicin in EBV-positive lymphoma. We expressed the major EBV protein, LMP1, in B-cell lymphoma cell lines and used them to screen 100 epigenetic modifiers in combination with doxorubicin. The screening results identified TCP, which is an inhibitor of LSD1. Further analyses revealed that LMP1 increased the activity of LSD1 to enhance stemness ability under doxorubicin treatment, as evidenced by colony-forming and ALDEFLUOR activity assays. Quantseq 3′ mRNA sequencing analysis of potential targets regulated by LSD1 in modulating stemness revealed that the LMP1-induced upregulation of CHAC2 was decreased when LSD1 was inhibited by TCP or downregulated by siRNA. We further observed that SOX2 expression was altered in response to CHAC2 expression, suggesting that stemness is regulated. Collectively, these findings suggest that LSD1 inhibitors could serve as promising therapeutic candidates for EBV-positive lymphoma, potentially reducing stemness activity when combined with conventional drugs to offer an effective treatment approach.